Polonistyczny dyskurs edukacyjny (tezy) - Sobolczyk, Piotr (Wydawnictwo Naukowe UAM, 2009)
The article raises the status of the literary scholarship for school discourse (in a specifically Polish context, but it can be generalized for all school communication about literature). It rejects the vision of a "minimized scientific literary scholarship discourse". This discourse is seen as wholly different, because it transports the scientific prototypes (understood in a cognitive manner) selectively and with a big delay, but also it combines them with the prototypes derived from the ethical (moral) and political discourses (like f.e. the ministerially programmed list of literary works for school). The author debates the question how to introduce the scientific prototypes from zero, how to construct a school synthesis of literary history and whether it is possible to avoid the technique of a "school heuresis" (i.e. asking questions which include answers in them etc.).
The Polish Literary Scholarship for School Discourse (Theses)